The domesticated Thai elephants as a sustainable resource : a comparative behavioural study on camp and zoo elephants - Wallmark, Charlotte (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
In this study the welfare among domesticated Asian elephants in Thailand (Maximus indicus) and Zoo elephants in Sweden and Thailand were investigated. The aim of the study was to see if elephants owned by local people and hired by camp managers showed a higher frequency of stereotypic behaviour than those owned by the camp, if zoo elephant perform a lot of stereotypic behaviours and what could be done to the decrease that level, if calves contribute to an increased welfare of their mothers and what could be done to ease the problems connected with musth in bulls. The study was performed at two different camps in Thailand; Thai Elephant Conservation Centre (TECC) and Surin Elephant Study Centre (SESC) and three zoos; Dusit Zoo, Borås Zoo and Kolmården Zoo. In total 39 individuals were studied and their behaviour was recorded each minute in a time interval protocol during four hours. Interviews were also carried out with mahouts and elephant keepers. No significant difference was seen in time-budget when comparing the two camps in Thailand. At Dusit zoo the level of stereotypic behaviour was higher than expected while little stereotypic behaviour was observed at the Swedish zoos. Altered feeding regimes will most probably decrease the level of stereotypic behaviour. Calves contribute to low level of stereotypic behaviour among their mothers and a wider variety of behaviours were seen. More money should be invested in research concerning musth control as musth related problems causes large animal welfare problems.